A postura plurilíngue e a criticidade no contexto do projeto de extensão adolescentes poliglotas - Arantes, Kássia Gonçalves (2024)
This research investigates how a plurilingual language teaching proposal can foster a plurilingual posture and the relationship between this posture and the promotion of criticality of teenage learners. Understood as the attitude of recognizing, opening up to and welcoming the society linguistic-cultural diversity and variation, the notion of plurilingual posture in this thesis intersects with the meaning of criticality through diversity, given that critique is here associated with the plural, i.e., which has the perception that nothing is unique or absolute. The theoretical grounds that underlie these and other basic concepts in the research come mainly from studies that cover language teaching and learning (Paiva, 2003; Leffa, 2005, 2016; Grilli, 2018), critical literacy (Menezes de Souza, 2011, 2011a; Duboc, 2012, 2017, 2018; Jordão, 2013; Monte Mór, 2013; Janks et al., 2014; Janks, 2018), multi and plurilingualism (Coste; Simon, 2009; Coste; Moore; Zarate, 2009; Altenhofen; Broch, 2011; Souza; Araújo e Sá, 2022), a plurilingual posture (Blanchet, 2014; Moore et al., 2020) and plural approaches to the teaching of languages and cultures (Kuchenbecker-Broch, 2012, 2014; Candelier et al., 2012; Candelier, 2017; Porsette, 2019; Sarsur Câmara, 2020). In methodological terms, this is an ethnographic case study carried out in the context of an outreach project at the Federal University of Uberlândia. The empirical data were generated in the first semester of 2022 through questionnaires and asynchronous activities applied to the students participating in the course, semi-structured interviews conducted with the participating professors, and field notes obtained during the classes’ observation. In addition, the course’s didactic material was also analyzed. For the analysis of the data from the perspective of its participants, this work is based on the model of Discursive Textual Analysis (Moraes; Galiazzi, 2016) and for the analysis of the course's didactic material, two analytical matrices were elaborated based on the notions of criticality and plurilingual posture in the context of the research. The data showed that there are many meanings attributed to the course by its participants, who perceive it from different perspectives, ranging from an opportunity for linguistic familiarization to a way to promote tolerance through exposure to linguistic-cultural diversity. Still regarding the perspective of the participants of the project, the results pointed to the perception of evidence both of the promotion of a plurilingual posture and the promotion of criticality within the project. Regarding the course's didactic material, the analysis demonstrated the existence of elements that also signal the promotion of a plurilingual posture and criticality, but at the level of potentialities, depending on the teacher’s approach.